1998
DOI: 10.1049/el:19980030
|View full text |Cite
|
Sign up to set email alerts
|

1.2 dB/cm gain in erbium:lutecium co-doped Al/P silica fibre

Abstract: We report a peak gain of 1.2dB/cm at 1535nm in an Erbium:Lutecium codoped Al/P/Si fibre fabricated using a standard MCVD and solution doping technique. This is the highest gain per unit length yet reported in an Erbium doped fiber amplifier. The incorporation of Lutetium into the glass is shown to reduce the erbium ion clustering within the fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In [4,[6][7][8], it was shown that the highest PCE in Er-doped fibers can be obtained using an aluminosilicate glass matrix with a concentration of Al 2 O 3 in excess of 3 mol.%. This glass matrix allow one to achieve a very high gain per length [9][10][11], which makes possible even building DFB Er-doped fiber lasers [12,13]. However, such a compound is not suitable for the fabrication of single-mode fibers with large core diameters because of the high (more than 0.14) core numerical aperture (NA).…”
Section: Introductionmentioning
confidence: 99%
“…In [4,[6][7][8], it was shown that the highest PCE in Er-doped fibers can be obtained using an aluminosilicate glass matrix with a concentration of Al 2 O 3 in excess of 3 mol.%. This glass matrix allow one to achieve a very high gain per length [9][10][11], which makes possible even building DFB Er-doped fiber lasers [12,13]. However, such a compound is not suitable for the fabrication of single-mode fibers with large core diameters because of the high (more than 0.14) core numerical aperture (NA).…”
Section: Introductionmentioning
confidence: 99%